Apartheid and Fragmented Protest in Contemporary Southern Africa: Life Goes On - Tagwirei, Cuthbeth (Routledge Contemporary Africa, 2025)
Apartheid and Fragmented Protest in Contemporary Southern Africa examines protest movements through the lens of Apartheid Studies, the first general theory of apartheid which explores how oppression, harm, injustice, poverty, loss, and inequality persist. The book argues that apartheid, which breaks the world of the oppressed into fragments, fomenting diverse experiences of oppression among its victims, frames the nature and course of protests by making them subject to its fragmentation. Protest is thus redefined as good neighbourly and demoted on account of its symbiotic relationship to apartheid. It is observed that the proliferation of protests does not preclude the persistence of apartheid. Rather, protest and apartheid are seen to be compatible. By examining protest hashtags on X from South Africa and Zimbabwe, the book explores and identifies the forms, relations, meanings, trajectories, and effects protests take, evoke, and embody as fragments subsisting in a fractured apartheid universe. It demonstrates how and why life goes on amidst protest, sheds light on the contradictions, paradoxes and complexities that characterise protest movements and invites conversations around protest as a paradigm in the context of apartheid. The book will be of interest to researchers across the fields of social movements, protests, sociology, African Studies, and communication and media studies.